PENGARUH REKAYASA MEDIA TANAM DAN PEMANGKASAN TERHADAP KUALITAS VISUAL DAN FUNGSIONAL RUMPUT Zoysia matrella - E. Junathan Muakhor E. Junathan Muakhor; Nizar Nasrullah; Afra DN Makalew (Jurnal Lanskap Indonesia, 2014)
Excellent condition of soccer field was influenced by grass condition as primary factor. Indonesian soccer field which is have international standard used manila grass (Zoysia matrella). At the moment, management of soccer field does not have any standard which can be use as reference.This research was aimed to study influence of difference composition planting medium, fertilizing, and mowing on the grass growth to fulfill the quality standars of visual and functional soccer field’s grass, and give recommendation of manila grass management related to planting medium, fertilizing, and mowing. This research conducted in University Farm of Bogor Agricultural University which located in Loji, Sindang Barang, West Bogor.Methods that used was planted the grass in plot area and gave the treatment according to experimental design. Observation data analysed by randomize group design with three factors to know the interaction of treatment to grass growth seen from visual and functional qualities parameter. The result shows interaction of three treatment factors was not significant. Significant influence was only detected in one or two treatment factors, but the significant influence was not seen at all in each observation variables. It was recommended for manila turfgrass using medium of sand, fertilizing 5 g/m2N, 2,5 g/m2 P2O5, and 2,5 g/m2 K2O once a months, and mowing at height of 2 cm